Neuromuscular Relaxation Using Anterior Leaf Gauge to Quick Guide the Condyles in Proper Position - Amal Abdallah A. Abo-Elmagd (Dentistry 3000)
To confirm the centric relation (CR), the leaf gauge can be used to load the TMJ. A load test will yield a negative result for a healthy TMJ. Nonetheless, the joint or muscles may be the reason of TMJ disorders if the patient experiences pain, tension, or tenderness, particularly in the region in front of the ear or nearby. In addition, the mandible can be in a centric relationship using a leaf gauge, which is made up of several plastic leaves. The leaf gauge helps the patient retrude the mandible by positioning it between the anterior teeth. The condyles tend to be moved against their menisci by the biting force. Therefore, this review study aims to describe the importance of the leaf gauge for neuromuscular relaxation to quick guide the condyles in CR position, to assist the recording of a reproducible jaw position during prosthodontic treatment.